2009
DOI: 10.1007/s11096-009-9301-4
|View full text |Cite
|
Sign up to set email alerts
|

The development of a sleep disorder screening program in Australian community pharmacies

Abstract: The development and pilot of this screening tool was successful. The prevalence of sleep disorders in the sampled population was high but generally consistent with previous studies on the general population. Furthermore, associations found may form a foundation for a clinical algorithm to identify those at a higher risk of having or developing a sleep disorder. Further work is required to validate this screening tool in the community pharmacy context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
47
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 35 publications
1
47
0
Order By: Relevance
“…However, the pharmacists in this study readily referred patients to see a GP following the unsuccessful management of insomnia. This might be due to several factors such as increased awareness about sleep disorders following several successful sleep health-promotion programs (Tran et al 2009;Fuller et al 2011) or the recognition by pharmacists of the limitations in their capacities to diagnose and manage insomnia as there are often increased options for management available through the GP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the pharmacists in this study readily referred patients to see a GP following the unsuccessful management of insomnia. This might be due to several factors such as increased awareness about sleep disorders following several successful sleep health-promotion programs (Tran et al 2009;Fuller et al 2011) or the recognition by pharmacists of the limitations in their capacities to diagnose and manage insomnia as there are often increased options for management available through the GP.…”
Section: Discussionmentioning
confidence: 99%
“…Although the implementation of non-pharmacological strategies was limited solely to advice concerning sleep hygiene, it does suggest that GPs and pharmacists are not averse to the concept. In fact research has shown that primary health practitioners do perceive the benefits of non-pharmacological therapies but often lack the resources and training to use those interventions (Tran et al 2009;Anthierens et al 2010). This is a potential issue facing the participants in our study given the lack of clarity on nonpharmacological treatment approaches for insomnia in the available management guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that pharmacists may be successfully trained to identify patients who are at risk for developing sleep disorders, and the community pharmacy is an ideal location for assisting "at-risk" patients. 4,14 Studies conducted by Tran et al 9 in 2009, and in 2011 by Fuller et al 14 have investigated the use of sleep assessment tools in Australian community pharmacies. These previous studies suggested that the use of a sleep tool in a pharmacy setting is viable and feasible.…”
Section: Discussionmentioning
confidence: 99%
“…7 Community pharmacies are often the most easily accessible health care locations in the community; therefore, they are often the first point of care for individuals with self-perceived sleep problems. 4 Studies have shown that pharmacists may be successfully trained to identify patients who are at risk for developing sleep disorders; 4,9 however, there are currently no specific tools available for use by Australian community pharmacists to determine those at risk. An assessment device or tool must be time-efficient, cost-effective, and practical, in order to be readily incorporated into the busy community pharmacy environment.…”
mentioning
confidence: 99%
See 1 more Smart Citation